Sustainability marketing strategies: exploring effective business to business (B2B) marketing strategies for industrial manufacturers approaching a low carbon future - Yong, Khai Pin (2024)
The marketing function within organizations plays a pivotal role in keeping companies abreast of changes in their broader and competitive environment (Hooley, 2020). Despite an abundance of literature on green marketing strategies to help business-to-consumer (B2C) firms build a competitive advantage around sustainability, there remains a noticeable gap in research regarding sustainability marketing in business-to-business (B2B) industrial firms. These industrial firms contribute significantly to global greenhouse gas emissions (EPA, 2020) and face mounting pressure from stakeholders to enhance sustainability efforts. Using case studies research based on insights derived from interviews with senior leadership teams of successful global industrial firms, the study explores B2B sustainability marketing strategies that industrial firms are adopting to achieve improved business performance, and investigates the challenges faced in implementing these strategies. The study also provides suggestions to overcome these challenges—a topic that has been relatively underexplored.